Traumatic stress, dissociation, and limbic irritability in patients with unipolar depression being treated with SSRIs - Bob, Petr; Susta, Marek; Gregusova, Alica; Jasova, Denisa; Raboch, Jiri; Mishara, Aaron (Psychological reports, 2010)
Recent evidence suggests that stressful experiences may be related to deficits in inhibitory functions and temporo-limbic epileptic-like activity. The latter may produce psychosensory seizure-like symptoms that may also appear in nonepileptic conditions. This study assesses whether the increased presence of the seizure-like symptoms in 113 unipolar depressive patients treated with SSRIs is associated with significantly more severe symptoms of depression, traumatic stress, and dissociation in comparison with 86 healthy controls. Results indicate that seizure-like symptoms in depressive patients have significant association with depression, symptoms of dissociation, and traumatic stress. This association suggests that processess generating seizure-like symptoms may be related to symptoms of depression, traumatic stress, and dissociation.
Keywords: dospělí; Dissociative Disorders; průzkumy a dotazníky; Female; Psychometrics; Life Change Events; Antidepressive Agents; Selective Serotonin Reuptake Inhibitors; psychometrie; Adult; ženské pohlaví; psychický stres; Surveys and Questionnaires; životní změny; lidé; Self Report; selektivní inhibitory zpětného vychytávání serotoninu; Male; depresivní poruchy; psychiatrické posuzovací škály; disociační poruchy; Depressive Disorder; lidé středního věku; mužské pohlaví; zpráva o sobě; antidepresiva; Middle Aged; Stress, Psychological; Serotonin Uptake Inhibitors; Psychiatric Status Rating Scales; Humans